The euro through the looking-glass: Perceived inflation following the 2002 currency changeover - Pete Lunn; David Duffy (The Economic and Social Research Institute (ESRI), 2010)
Following the Euro changeover in January 2002, consumers across the Euro Area perceived a sharp rise in inflation, in contrast to official figures. Several theories have been advanced to explain this apparent economic illusion, but they struggle to account for its striking scale and persistence. We offer an alternative account, based on the premise that the currency changeover increased consumers' perceptual error when assessing the value of monetary amounts. Under plausible assumptions, this would lead them to experience a loss of purchasing power. We confirm two empirical hypotheses in support of the theory: (1) the extent of overestimation of inflation was strongly associated with subjective difficulty using the Euro; (2) there was a simultaneous downward shift in expected inflation. Our results imply that currency changeovers are not simple matters of numerical conversion.
Keywords: 330; Euro changeover; uncertainty; inflation perceptions; inflation expectations; consumer behaviour; Währungsumstellung; Inflationserwartung; Risiko; Konsumentenverhalten; Euro; EU-Staaten